Peningkatan Motivasi Belajar Pendidikan Agama Islam Melalui Metode Pemecahan Masalah di Sekolah Menengah Pertama: Enhancing Learning Motivation in Islamic Religious Education Through Problem-Solving Methods in Junior High School - Nurpriatna, Ade (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2023)
This classroom action research examines the effectiveness of Problem Solving method in enhancing learning motivation for Islamic Religious Education (PAI) among junior high school SMP Iko Anata Putra, Nagrak, Sukabumi students. Conducted in two cycles with 30 eighth-grade participants, the study employed observation, achievement tests, and motivation questionnaires. Findings revealed substantial improvements across key indicators: instructional quality increased from 69% to 87%, student engagement rose from 62% to 82%, and learning outcomes improved from an average score of 65 (40% mastery) to 78 (85% mastery). Motivation levels showed 13% overall growth, with notable increases in intrinsic motivation components including learning desire (66% to 79%) and activity interest (67% to 80%). The research demonstrates how Problem Solving fosters active learning environments, develops critical thinking skills, and strengthens religious value internalization. These results suggest the method's potential for broader application in PAI instruction, particularly in addressing motivation challenges. Further studies should explore technological integration and long-term cognitive-affective impacts of this approach.